The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pr9081311
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Total Phenolic Content, Antioxidant Capacity, Fe and Cu Content from Tea Plant Samples at Different Brewing Times

Abstract: The purpose of this study was to investigate the antioxidant capacity of different tea plant: mint, linden, chamomile, St. John’s wort, green and black tea in relation to total phenolic content. The antioxidant capacity of the tea infusions at different brewing times was determined using DPPH assay while the total phenolic content (TPC) was assessed using the modified Folin-Ciocalteu method. The results showed that there were significant statistical differences in antioxidant capacity depending on infusion tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…Significant correlations were also established between DPPH and TotF contents ( R 2 = 0.9520). Our results agree with other studies that reported a relationship between antioxidant capacity and total phenolic compound content [ 34 , 51 , 52 , 53 ].…”
Section: Resultssupporting
confidence: 93%
“…Significant correlations were also established between DPPH and TotF contents ( R 2 = 0.9520). Our results agree with other studies that reported a relationship between antioxidant capacity and total phenolic compound content [ 34 , 51 , 52 , 53 ].…”
Section: Resultssupporting
confidence: 93%
“…A strong association between polyphenols and antioxidant properties exists [ 41 , 42 , 43 , 44 ]. The formulations were subjected to antioxidant analysis using ABTS, DPPH, FRAP, and CUPRAC methods in order to gain a better understanding of their antioxidant activity ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds, including flavonoids, are antioxidants due to their ability to scavenge and/or reduce high-energy radicals. It is confirmed that total phenolic content correlates with antioxidant activity [ 12 , 13 ]. The antioxidant activity of phenolic compounds is mainly due to their redox properties, which can play an important role in neutralizing free radicals.…”
Section: Introductionmentioning
confidence: 88%